Self Efficacy of Indonesian English Foreign Language Learners in Speaking English - Haris Mulyanto; Encik Shahzool Hazimin Bin Azizam; Jailani Jusoh (International Journal of English and Applied Linguistics (IJEAL), 2022)
Self-efficacy is the condition of someone's capability to complete a task in a significant manner that impacts the development of human achievement, especially for students who are learning a foreign-speaking language system. It is one of the vital aspects of improving language learning. Thus, it is a crucial factor in building self-confidence in spoken English. Furthermore, this study is intended to analyze the Indonesian English Foreign Language Learner (EFL) in speaking English. The method used in this study is a literature review to reveal the impact of self-efficacy on Indonesian English Foreign Speakers. The data were collected by analyzing the journal, sources, and articles of Indonesian scholars conducting similar research. The widespread self-efficacy influence displayed in the form of the investigation, the numbers of Indonesian students participation, and the result of achievements changed among the high and low-efficacy of Indonesian English Foreign Language Learner (EFL) in speaking English within the study.